Optimal scheduling of the CSP–PV–wind hybrid power generation system considering demand response - Zhao, Qingsong; Yang, Beijia; Ma, Hui; Liu, Gang; Xu, Jianyuan (Frontiers in Energy Research, 2024)
In order to solve the problem of high proportion of wind and photovoltaic(PV) abandonment in new energy system, an optimal dispatching method of concentrated solar power(CSP)-PV-Wind hybrid power generation considering demand response is proposed. Firstly, on the basis of the combination of wind and PV power stations and CSP stations, electric heating(EH) devices are used to convert unconsumed wind and PV power into thermal energy stored in the thermal storage system of the CSP station. Secondly, based on the difference in response time and response volume of customers ,a stepped incentive-based demand response(IBDR) approach is introduced. Thus, a CSP-PV-Wind power optimal dispatch model that taking into account IBDR is established to achieve coordinated source-load dispatch. Finally, cplex solver is invoked to optimize day-ahead scheduling with the goal of the lowest system comprehensive cost. Example analysis is used to confirm the proposed method's usefulness of enhancing the system's wind and PV power consumption capacity and reducing the system's comprehensive cost.